IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN TEKNIK KLARIFIKASI NILAI MATA PELAJARAN PPKN DI SMA - Herningsih; Ihsan (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2020)
Research that aims to determine the implementation of problem-based learning model with values ??clarification techniques on the learning PPKn of class X SMA.This study was a quantitative approach with the quasi experimental research methods.The study design was a randomized control group pretest posttest. The data were collected using cognitive test, observation, and  questionnaire. Data were analyzed using t-test and analysis of variance (Anova)and gain score. The research finding that the application of problem based-learning use with values ??clarification techniques in teaching civic is more effective on civic learning. It can be seen from the outcomes, that the significance level which is lower  than 0.05 (p = 0.000 <0.05) and the gain score. The experimental class obtained the gain score of 0.57 which is in the "medium" category of effectiveness. The control class obtained gain score of 0.30 which is in the "low" category of effectiveness.